WOMEN’S LABOUR MARKET ACTIVITY IN THE AGRICULTURE SECTOR IN POLAND AND EUROPEAN UNION IN 2016 - Matuszewska-Janica, Aleksandra (Proceedings of the International Scientific Conference "Economic Sciences for Agribusiness and Rural Economy", 2018)
The European authorities pay particular attention to agriculture and employees in this sector. Women represent more than 33% of this group in the European Union. A significant number of actions are targeted at women from rural areas, having regard to the mentioned issues and specific situation of women in the labour market. Therefore, it requires in-depth analyses. The main aim of the presented study is to assess the diversity of the situation of women working in agriculture across the EU. The quantitative analysis allows to indicate similarities and differences among EU states in the current structure of women’s employment in this sector. In the analysis, the k-mean method is applied with the Labour Force Survey data from the year 2016. The study refers to 28 EU states and a group of women aged 20–64. The obtained results indicated that we have a large proportion of self-employees in agriculture. However, we observe a larger percentage of those who create jobs for others states that are better economically developed. This analysis confirms the findings that the Polish structure of female employment is closer to those in the Mediterranean countries. Poland is assigned to one cluster with Greece. This group is distinguished by several factors. Firstly, it contains a high proportion of people employed in agriculture with a relatively small share of part-timers. Secondly, it is a very high rate of self-employed with a very low proportion of those who create jobs for others.